BINAA AL-KAFAA'AH AL-TAWAASULIAH FI TA’LIIM AL-LUGAH AL-‘ARABIAH WA TA’ALUMIHAA BI AL-SIYAAQ AL-IJTIMAA’I BI SEKARBELA FI MADINAH MATARAM - Mujiburrahman Mujiburrahman; Dedy Wahyudin (Universitas Islam Negeri Mataram, 2025)
This research aims to examine the construction of communicative competence in the teaching and learning of Arabic within the social context of the Sekarbela society in Mataram. They are famous for their long tradition of studying Arabic linguistics, including morphology, syntax, and rhetoric. This applies not only to educational institutions but also to society as a whole. The researchers sought to investigate whether it is possible to benefit from such a social context to build communicative competence in the Arabic language, by applying functional theory, which imposes the existence of an appropriate context for the natural use of the Arabic language in various linguistic situations. Multiple experiments have shown that teaching Arabic to non-native speakers by focusing on the practical aspect of the Arabic language strengthens learners mental, psychological and social abilities in dealing with the Arabic language, as stated in many studies. This study adopted a qualitative research approach using observation, interviews, and documentation techniques. The research results showed that the effectiveness of Arabic language learning is greatly influenced by the integration of local social and cultural contexts into the teaching process. The use of a communicative approach and social context-based teaching methods contributed to improving students' ability to understand and use Arabic more naturally. Additionally, the study recommends developing a curriculum that aligns with students' social communication needs to make the learning process more effective and practical.